Features of morphofunctional changes in periodontal tissue in patients with chronic parodontitis and periodontitis. - Kernytskyy, R. V.; Guluk, A. G.; Gorjanova, N. O.; Ulianov, V. O. (Морфологія / Morphologia / Morfologìâ, 2012)
The features of the morphological changes in the periodontal tissues in the cervical and periapical areas in different forms of chronic parodontitis and periodontitis were studied. Under supervision there were patients diagnosed with chronic granulomatous periodontitis and chronic parodontitis. Data of investigation suggest the existence of differences in morphological and functional properties of the periodontal tissues of chronic periodontitis. Patients with chronic granulomatous periodontitis can be divided into three groups: patients with a predominance of inflammatory changes, with a predominance of degenerative changes and mixed form. On X-ray imaging to set histological differentiation into subgroups was not possible. These data suggest the existence of differences of morphological and functional changes in the properties of periodontal tissue in chronic periodontitis, namely the prevalence of inflammatory or degenerative changes that require a differentiated approach to the treatment of chronic periodontitis include data pathomorphological study.